Urinary Adrenomedullin Level in Children With Acute Pyelonephritis Before and After Treatment (Iranian Journal of Kidney Diseases, 2013)
Introduction. Adrenomedullin (AM) is a 52-amino acid peptide that causes vasodilatation by increased synthesis of nitric oxide. Its production by different cells such as cardiac myocytes, smooth muscle, endothelial, and oncogenic cells is stimulated by inflammatory processes. It has been shown that in the presence of inflammation in the urinary system, concentration of AM increases. In this study, we measured urinary AM in children with acute pyelonephritis before and after treatment and compared its level with that in healthy children. Materials and Methods. In a case-control study, 31 children with clinical and paraclinical documentation of pyelonephritis (case group) and 30 healthy children without pyelonephritis or other infections (control group) were studied. Urinary AM were measured on spot urine samples by high-performance liquid chromatography, and creatinine was measured by spectrophotometry to report the AM-creatinine ratio. Results. Urinary AM- creatinine ratios were 61.3 ± 119.4 pg/mg and 4.26 ± 11.4 pg/mg, respectively, in the case and control groups (P = .01). After treatment of pyelonephritis in the patients of the case group, this ratio decreased to 13.1 ± 21.9 (P = .048).  The coefficient correlation between urinary AM and leukocytes count was 0.252 (P = .17). Urinary AM levels were 1896 ± 1748 pg/dL and 391 ± 477 pg/dL in the patients with 4+ versus negative C-reactive protein levels, respectively (P = .008). Conclusions. Urinary AM increases in the course of pyelonephritis and decreases significantly after treatment.